Online Learning: student participation and satisfaction / Zarirah Zamakhsari, Arifi Ridzuan - Zamankhsari, Zarirah; Ridziuan, Arifi (UiTM Press, 2017)
This research focuses on student participation and satisfaction toward online learning at Universiti Teknologi MARA, Pahang. This has become a major concern of lecturers because of the challenge in engaging students in online learning, thus, creating a need to study the activities used in online learning. In addition, the poor participation of students in online learning activities has created a major problem in implementing online learning. Three research objectives were developed for this research; the first attempts to identify the type of online learning activities among students; the second investigates the approaches used by lecturers to encourage student participation in online learning; and the third attempts to identify the level of satisfaction among students toward online learning. The findings revealed that the online learning activities preferred by students are group discussion, followed by online tests or quizzes and searching for online notes. Furthermore, uploading of assignments by lecturers in the group forum was found to be a favored approach to encourage student participation in online learning.